BEHAVIORAL CHARACTERISTICS OF CHILDREN WITH SICKLE CELL DISEASE - Fellipe Bondança Pereira; Glaura César Pedroso; Rosa Miranda Resegue; Marcos Vinicius Vieira Ribeiro; Mary Hokazono; Josefina Aparecida Pellegrini Braga (Sociedade de Pediatria de São Paulo, 2020)
ABSTRACT Objective: To evaluate sociodemographic and clinical aspects of children with sickle cell disease (SCD) and their behavioral characteristics. Methods: Interview with parents of patients with SCD from four to ten years old, addressing socioeconomic aspects and other health conditions, and using the Strengths and Difficulties Questionnaire (SDQ). Clinical data were obtained from medical records. Exclusion criteria were the use of hydroxyurea, previous diagnosis of stroke, chronic encephalopathy and/or intellectual disability. Results: 45 patients (19 girls and 26 boys) were assessed. The median age was seven years. Diagnosis of SCD: 26 hemoglobinopathy SC; 19 hemoglobinopathy SS. Socioeconomic class: D: 24.4%; C2: 44.4%; C1: 28.9%; B2: 2.2%. Clinical history: acute chest syndrome: 40%; transfusions: 66.7%; hospitalizations: 82.2%. SDQ findings: 88.9% clinical impact (emotional subscale: 68.9%); total score: impact in 48.9%. It was not possible to establish a relation between the severity of the disease and the results of the SDQ. Regarding socioeconomic class: among individuals of classes B2 and C1, 21.4% had impact at the total score; in classes C2 and D, this percentage was 61.3%. Regarding the schooling of the head of the family, with Elementary School at least, 39.3% of the children had impacts; for fewer education, this percentage was 64.7%. Conclusions: Behavioral impacts are highly prevalent in children with SCD. Individuals in socioeconomic classes C2 and D suffered more behavioral impacts than individuals in classes B2 and C1.